2016
DOI: 10.1371/journal.pone.0167240
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Isomers and Metabolites Exhibit Distinct Affinity and Activity at Cannabinoid Receptors: Potential Scaffold for Drug Development

Abstract: Tamoxifen (Tam) is a selective estrogen receptor (ER) modulator (SERM) that is an essential drug to treat ER-positive breast cancer. Aside from known actions at ERs, recent studies have suggested that some SERMs like Tam also exhibit novel activity at cannabinoid subtype 1 and 2 receptors (CB1R and CB2Rs). Interestingly, cis- (E-Tam) and trans- (Z-Tam) isomers of Tam exhibit over a 100-fold difference in affinity for ERs. Therefore, the current study assessed individual isomers of Tam and subsequent cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Although this and previous studies clearly demonstrate that SERM-scaffolds may be useful for synthesis of selective CB 1 and/or CB 2 cannabinoid ligands (Kumar and Song, 2013; Prather et al, 2013; Ford et al, 2016), before novel compounds can be useful therapeutically, drugs in this class must first be designed that lack ER affinity to prevent off-target effects. Importantly, RID-B is only a first generation of many ridaifen (RID) compounds that are tamoxifen derivatives, developed to reduce ER affinity, yet maintain cytotoxic effects in cancer (Shiina et al, 2008; Guo et al, 2013b).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Although this and previous studies clearly demonstrate that SERM-scaffolds may be useful for synthesis of selective CB 1 and/or CB 2 cannabinoid ligands (Kumar and Song, 2013; Prather et al, 2013; Ford et al, 2016), before novel compounds can be useful therapeutically, drugs in this class must first be designed that lack ER affinity to prevent off-target effects. Importantly, RID-B is only a first generation of many ridaifen (RID) compounds that are tamoxifen derivatives, developed to reduce ER affinity, yet maintain cytotoxic effects in cancer (Shiina et al, 2008; Guo et al, 2013b).…”
Section: Discussionmentioning
confidence: 78%
“…Based on the structural similarity of RID-B to tamoxifen (Fig. 1), and our past reports that tamoxifen exhibits moderate affinity for cannabinoid receptors (Prather et al, 2013; Ford et al, 2016), a competition receptor-binding screen was conducted. From this initial binding screen, it was observed that RID-B (1 μM) produced > 50% displacement of the CB 1 /CB 2 radioligand [ 3 H]-CP-55,940 (0.2 nM) from human CB 1 and CB 2 receptors stably expressed in CHO cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamoxifen is an anti-estrogen drug used in the treatment of breast cancer. Hepatotoxicity is a commonly reported side effect of tamoxifen (Ford et al, 2016; Henderson et al, 2016; Khuroo et al, 2014; Lin et al, 2014; Tabassum et al, 2006; Villegas et al, 2016). In our study, mitochondrial impairment and disruption of cell membrane integrity were the main mechanisms of tamoxifen-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of ROS inside cells decreases the glutathione level resulting in oxidative stress and causes mitochondrial impairment leading to apoptosis (Cabezas, El‐Bachá, González, & Barreto, ; Jin et al., ; N. Li et al., ; Moon, Lee, Park, Geum, & Kim, ). Tamoxifen is an anticancer drug with hepatotoxicity as its commonly reported side effect (Ford, Franks, Radominska‐Pandya, & Prather, ; Henderson, Wendy, & Kim, ; Khuroo et al., ; Lin et al., ; Tabassum, Rehman, Banerjee, Raisuddin, & Parvez, ; Villegas et al., ). Mitochondrial impairment is known to be the main mechanism of tamoxifen‐induced toxicity (Lee, Kang, Lee, & Kim, ; Tabassum et al., ; Tolosa et al., ; Tolosa, Carmona, Castell, Gómez‐Lechón, & Donato, ).…”
Section: Commentarymentioning
confidence: 99%